The United Arab Emirates as a global donor: what a decade of foreign aid data transparency reveals - Logan Cochrane (7822049) (2021)
The United Arab Emirates (UAE) has become a leading contributor of foreign aid, in terms of percentage of gross national income as well as in total amount. Historically, Emirati aid was opaque, and little was known about the foreign aid portfolio. This changed after 2009 when the UAE began to submit detailed, project-level data to the Development Assistance Committee of the OECD. Based on a decade of aid transparency, this article carries out an examination of the political economy of aid provided by the UAE, comparing its portfolio to other donor countries. Particular attention is paid to analyzing three primary recipients of its aid (Egypt, Serbia and Yemen) and the implicit motivations driving those decisions. The majority of Emirati aid to these three countries was granted as general budgetary support, often in tandem with efforts to achieve political, economic and/or military aims. Based on the findings, an evaluation is made regarding Emirati narratives of South-South cooperation and its seeking of mutual benefit as well as critiques put forward within the literature countering this. In addition to critically assessing the details of an under-researched aid portfolio, this paper highlights areas for further study to deepen our understanding of the UAE’s foreign aid. Other Information Published in: Development Studies Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/21665095.2021.1883453